THE EFFECT OF BOARD RACE GAME ON STUDENTS’ VOCABULARY MASTERY (A STUDY OF TENTH GRADE STUDENTS OF SMK NEGERI 1 SIPIROK 2019/2020 ACADEMIC YEAR) - naza muddin baharsyah (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract: The objectives of this research is to know there is a significant effect of board race game on students’ vocabulary mastery at tenth grade students of SMK Negeri 1 Sipirok. This research uses experimental method with pre-experimental research design; one group pre-test post-test design. The population is all of the tenth grade students which consist of 160 students. Technique sampling that used on this research is cluster sampling and the number of the sample consists of 28 students. In collecting the data, the researcher uses observation sheet to get the data of the application of board race game and test to get the data of the students’ vocabulary mastery. The researcher uses statistic process in analyzing by using t test formula. Based on the data that had been analyzed, the result of data analyzing showed that t count is higher than t table (t count 2.99 > t table 2.05). So, the hypothesis is accepted. It means that there is a significant effect of board race game on students’ vocabulary mastery at tenth grade students of SMK Negeri 1 Sipirok. Keywords: board race game, vocabulary mastery. Abstrak: Tujuan penelitian ini adalah untuk mengetahui apakah ada sebuah pengaruh yang signifikan dari board race game terhadap penguasaan kosakata siswa di kelas sepuluh SMK Negeri 1 Sipirok. Penelitian ini menggunakan metode eksperimental dengan rancangan penelitian pre-experimental; one group pre-test post-test design. Populasi penelitian terdiri dari 160 siswa di kelas tujuh. Tehnik penarikan sampel yang digunakan dalam penelitian ini adalah penarikan sampel cluster sampling dan jumlah sampel terdiri dari 28 siswa. Dalam pengumpulan data, peneliti menggunakan lembar observasi untuk menjaring data dari pengaplikasian board race game dan tes untuk menjaring data mengenai pencapaian pada penguasaan kosakata. Peneliti menggunakan proses statistic dalam analisis data, yaitu rumus tes t. Berdasarkan data yang telah di analisis, hasil analisis data menunjukkan bahwa t hitung lebih besar daripada t table (t hitung 2.99 > t table 2.05). Jadi, hipotesis diterima. Hal ini berarti ada sebuah pengaruh yang signifikan dari board race game terhadap penguasaan kosakata siswa di kelas sepuluh SMK Negeri 1 Sipirok. Kata Kunci: board race game, vocabulary mastery.